2016
DOI: 10.1371/journal.pone.0165419
|View full text |Cite
|
Sign up to set email alerts
|

EGF Functionalized Polymer-Coated Gold Nanoparticles Promote EGF Photostability and EGFR Internalization for Photothermal Therapy

Abstract: The application of functionalized nanocarriers on photothermal therapy for cancer ablation has wide interest. The success of this application depends on the therapeutic efficiency and biocompatibility of the system, but also on the stability and biorecognition of the conjugated protein. This study aims at investigating the hypothesis that EGF functionalized polymer-coated gold nanoparticles promote EGF photostability and EGFR internalization, making these conjugated particles suitable for photothermal therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 58 publications
4
36
0
Order By: Relevance
“…In non‐illuminated cells, EGF induces visible EGFR activation followed by receptor internalization which is in agreement with literature . The work by Silva et al confirmed that such enhancement of green fluorescence was due to the formation of the EGFR‐EGF complex, as the presence of an antibody against EGFR has prevented EGF binding to EGFR and no enhancement of green fluorescence at the cell membrane level and complex internalization were observed .…”
Section: Discussionsupporting
confidence: 88%
“…In non‐illuminated cells, EGF induces visible EGFR activation followed by receptor internalization which is in agreement with literature . The work by Silva et al confirmed that such enhancement of green fluorescence was due to the formation of the EGFR‐EGF complex, as the presence of an antibody against EGFR has prevented EGF binding to EGFR and no enhancement of green fluorescence at the cell membrane level and complex internalization were observed .…”
Section: Discussionsupporting
confidence: 88%
“…In turn, surface plasmon resonance causes a strong absorption of the incident light, and a portion of this energy is dissipated as local heat, along with the release of molecules from the AuNP surface. Due to these properties, AuNPs are applied in nanomedicine for detection, using techniques such as surface-enhanced Raman spectroscopy [ 35 ] or surface-enhanced fluorescence [ 36 ]; as plasmonic sensors [ 37 ]; for drug transport and release [ 38 40 ]; or in photothermal treatments [ 41 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Light is another factor that induces protein conformational changes. UV excitation of the protein's aromatic pool, i.e., tryptophan (Trp), tyrosine (Tyr) and phenylalanine (Phe), also leads to protein conformational changes [16]. UV light induced photo-oxidation of,…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Proteins have a specific interaction within a solvent environment that affects their dielectric relaxation mechanisms [31]. In polar environments there is a reorganization of the solvent's polar molecules along the electric field lines generated by dipoles in the protein [32] and as a consequence, the system relaxes and the protein will emit at longest wavelengths [16].…”
Section: Conformational Analysis Using Fluorescence Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation